Improving Teacher Work Engagement Through Compensatory Satisfaction and Psychological Well-Being - Mardhotillah, Hafsah; Rochanah, Siti; Matin, Matin (Jurnal Pendidikan Progresif, 2021)
Abstract: Improving Work Engagement Through Compensatory Satisfaction and Psychological Well-Being. Objecticves: This study aims to identify the effect of compensation and psychological well-being on work engagement for private elementary school teachers during the pandemic. Methods: This study employed a quantitative approach with multiple linear regression analysis. The data retrieval technique used a Instrument developed from the utrech work engagement scale, a ryff psychological well-being scale and a compensation scale. Sample selection was done by using purposive cluster sampling technique. Research sampel is 408 teachers of private elementary schools in Karawang Regency. Findings: The results of this study confirm that: (1) Compensation had a significant effect on teachers work engagement, (2) Psychological well-being had a significant effect on teachers work engagement, and (3) Compensation and psychological well-being simultaneously affected teachers work engagement by 50.6%. Conclusions: It is concluded that work engagement is influenced by compensation and psychological well-being. Therefore, these two variables need to be considered in increasing teacher work engagement. Keywords: psychological well-being, compensation, work engagement DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202116